High/Low Gain Rectangular Dielectric Resonator Antenna for WLAN Applications - Behloul, A; Messaoudene, I; Chouti, L; Benghalia, A (International Journal of Natural Sciences Research, 2016)
In this paper, a novel integrated dual-port rectangular dielectric resonator antenna (DRA) is presented for 802.11a WLAN system applications. The antenna structure is formed by integrating the concept of antenna array with a single DRA element to produce a radiation characteristic necessity. The array is composed of four identical rectangular DRA elements placed on a horizontal ground plane and separated by a distance of 0.54λ at design frequency of 5.97 GHz, excited through rectangular shaped aperture slots by a microstrip transmission line from port 1. The central element fed from port 2 by 50 Ohm microstrip line via a slot etched on the ground plane. The designed proposed antenna sized of 60×80×0.672 mm3 operates over the frequency band between 5 and 6 GHz for VSWR < 2. The simulated average gain is 10.55 dB for port 1, and 5.92 dB for port 2. Simulations are performed using both CST Microwave studio employing the Finite Integration Technique (FIT) and Ansoft HFSS employing the Finite Element Method (FEM). Good agreement is obtained for main antenna characteristics such as the reflections coefficient and transmission coefficient. The results confirm that the proposed structure suitable for reconfigurable gain applications with good isolation between the two structure ports.